Oil and the new international economic order : proceeding of the 1980 annual conference of the Nigerian Economic Society - Nigerian Economic Society Annual Conference (Ibadan : The Nigerian Economic Society, 1980)
This book contains conference proceeding for the 1980 annual meeting of the Nigerian Economic Society.
Includes list of participants
asm 22/01/2019
Loans
Keywords: Petroleum industry and trade; International economic relations; Economic history; Nigeria